VLF-LF Radio Signals Collected at Bari (South Italy): a Preliminary Analysis on Signal Anomalies Associated with Earthquakes - BIAGI P. F.; PICCOLO R.; CASTELLANA L.; MAGGIPINTO T.; ERMINI A.; MARTELLUCCI S.; BELLECCI C.; MOLCHALOV A.; HAYAKAWA M.; OHTA K.; CAPOZZI, VITO GIACOMO; PERNA, GIUSEPPE (2004)
At the beginning of 2002 an OmniPAL receiver was put into operation at the Department of Physics of Bari University (Southern Italy). The electric field strength of five VLF-LF signals transmitted from United Kingdom (f=16kHz), France (f=20.9kHz), Germany (f=23.4kHz), Iceland (f=37.5 kHz) and Italy (f=54 kHz) has been monitoring with a 5 s sampling frequency. In a first step we reduced the amount of the data taking one datum each 10 min (mean of the 5 min raw data) and then we smoothed these data by a running adjacent averaging over 7 days. Analysing the trends we obtained, we revealed at first in the signal from the Italian transmitter two clear intensity decreases in April 2002 and in August-September 2002. At these times we observed earthquakes with M=4.3 and M=5.6 respectively near the transmitter-receiver path and a precursory effect in the previous decreases appeared. Then, we noted that all of the five radio trends in the time interval March 2002-February 2003 are more disturbed than in other periods; in particular an evident simultaneous decrease appears in January-February 2003. We propose that these disturbances are related to general excitation of the margin between the African and European plates. In a second step we examined the terminator time (evening) changes for the Italian transmitter in July-September 2002, and we found significant deviations from the mean value at the end of August, which is supportive for some precursory ionospheric signature of earthquakes.